Phonetic and semantic structures in the Hungarian translations of Ulysses - Mitruly, Árpád (Revista Letras, 2024)
This study delved into the challenges and intricacies of intertextuality present in Hungarian translations of James Joyce’s Ulysses, focusing particularly on Shakespearean references and analyzing intertextual linguistic data between English and Hungarian equivalents. It examines the applicability of Antoine Berman and Paul Bensimon’s retranslation hypothesis, alongside phonetic and semantic structures. By examining intertextual references, the study elucidates the challenges faced by Joyce’s Hungarian translators and offers insights into the source text’s reception. Allusions and cultural references in Ulysses can be linked back to Shakespeare’s oeuvre. Through meticulously chosen text segments, the study supports the notion that retranslations adhere more closely to the original text, employing a foreignizing approach, while first translations tend towards domestication. Categorized according to semantic and phonetic attributes, segments from Shakespearean works and their Hungarian counterparts highlight nuances of intensity and expressivity. Analysis of Shakespearean intertextualities reveals a close link between translation and retranslation, suggesting that retranslations maintain the source text’s characteristics more faithfully.